Pengaruh Elektroakupuntur Titik Weishu (BL 21) dan Zusanli (ST 36) terhadap Perbaikan Mukosa Pylorus Tikus yang Dipapar Bising Intermittent - Bawono, Paksi Suryo; Balgis, .; Handayani, Selfi (Nexus Biomedika, 2014)
Background: Noise is a stressor which can negatively effect to the body. Intermittent noise will give more influence to stomach, namely in the form of an increase in the production of stomach acid that interferes with the mechanism of gastric cytoprotection. Electro-acupuncture on Weishu (BL 21) and Zusanli (ST 36) acupoints has potential to repair damaged mucosal pylorus due to noisy stress. This research aimed to know the influence of electro-acupuncture on Weishu (BL 21) and Zusanli (ST 36) acupoints against pyloric mucosal repair of rats exposed to intermittent noise. Methods: This study was laboratory experimental group post-test only designs. Subjects were Rattus norvegicus with inclusion criteria male, Wistar strain, weight 250-300 g, and 2 months old. Subjects were randomly drawn 28 rats, divided into: Group K (control), P1(no time to recover and no electro-acupuncture stimulation), P2 (given time to recover naturally for 30 days) and P3 (stimulated with electro-acupuncture). After adapted for 7 days all subjects of the groups, except group K, were exposed to intermittent noise at 95 dB with one-hour exposure settings, one-hour break for 12 hours within 14 days. Stimulation on Weishu acupoint (BL 21) was conducted at 2-3mA, 1ms duration, 50Hz frequency for 15min, 3mm pierced into the skin. While Stimulation on Zusanli accupoint ( ST 36 ) was done at 2-3mA with 0.5ms duration at 4Hz frequencies for 20min, plugging 3mm into the skin. Next day, all of the subjects were sacrificed by cervical dislocation. Pylorus were taken and histological preparations were made by HE staining. The results were assessed with the Barthel index. Henceforth, the data obtained were tested by statistical tests One Way ANOVA ( α = 0.05 ) followed by LSD . Results: Based on statistics analysis, there was a significant difference between the groups K-P1, K- P2, K-P3, P1-P2 and P1-P3. In contrast, there was no significant difference between P2 and P3. Conclusion: There was not statistically proven effects of Weishu point electro-acupuncture (BL 21) and Zusanli (ST 36) against gastric mucosa repair rat intermittent noise, but when seen in the data were the result of a decrease in the degree of mucosal damage. Keywords: Electro-acupunctur Weishu (BL 21) and Zusanli (ST 36) acupoints , intermittent noise , pylorus